MANAJEMEN PUBLIC RELATION DALAM MENINGKATKAN CITRA LEMBAGA DI SMA NEGERI UNGGUL PIDIE JAYA - Salamuddin Salamuddin; Hera Yanti; Sari Rizki (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study aims to describe the management of public relations in improving institutional image at SMA Negeri Unggul Pidie Jaya. The background of the study is based on the increasing competition among educational institutions and the growing public demand for service quality, information transparency, and school credibility. In this context, public relations is viewed as a strategic managerial function that plays an important role in building public trust and a positive institutional image.This research employed a qualitative approach with a descriptive method. The research site was purposively selected at SMA Negeri Unggul Pidie Jaya, Pidie Jaya Regency. Data were collected through in-depth interviews, observation, and document analysis. The research subjects included the principal, vice principals in the areas of curriculum, student affairs, and public relations, as well as teachers and students. Data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing.The findings indicate that public relations management at SMA Negeri Unggul Pidie Jaya is implemented systematically through the functions of planning, organizing, implementation, and supervision and evaluation. Public relations planning is developed based on the school’s vision and public needs, organizing is carried out through clear task distribution and coordination, implementation is realized through activity publication and active communication with the public, and evaluation is conducted continuously through internal meetings and community feedback. The implementation of effective public relations management contributes positively to the improvement of institutional image, as reflected in school trust and reputation, openness and transparency of communication, and the quality of services and interactions with the public.